Pengaruh Komunikasi dan Motivasi serta Lingkungan Kerja terhadap Kinerja Karyawan pada PT Asta Rekayasa Unggul - NURFADILAH NURFADILAH; Robiansyah Robiansyah; Syaharuddin Y Syaharuddin Y (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Nurfadilah. 2018. Effect of Communication and Motivation and Work Environment on Employee Performance of PT Asta Rekayasa Unggul, under guidance. As Advisor I, Mr. Robiansyah and Mr. Syaharuddin as Advisor II.The purpose of this study was to examine the influence of Communication, Motivation and Work Environment on Employee Performance of PT Asta Unggul Rekayasa. Research data collection uses a census method in which all population of 53 people is used as samples. This study uses multiple linear regression analysis with SPSS as a calculation tool.The results of the study show  that there is a positive and significant effect between communication on employee performance. And there is a positive and significant influence between motivation and employee performance. And there is a positive and significant influence between the work environment on employee performance.